The effect of guided discovery instructional strategy on grade nine learners' performance in chemical reactions in Mankweng circuit, South Africa - Israel Kibirige; Rebecca Mampageti Maake (OmniaScience, 2021)
Teaching strategies play a vital role in improving learners' performance. This study investigated the effect of Guided Discovery Instructional Strategy (GDIS) on Grade nine learners' performance in chemical reactions and determined the effect of GDIS on gender. A quasi-experimental design was used with a sample comprised 75 Grade nine learners purposively selected from two schools in Mankweng Circuit based on Grade 12 poor performances. Learners were randomly assigned to the Experimental Group (EG) (N = 40) and Control Group (CG) (N = 35) taught for two weeks using GDIS for EG, and Talk and Chalk Method (TCM) for CG. The results show that there were statistically significant differences between CG post-test (T-test: t(78) = 19.89; p = 0.05); Cohen d = 4.40 for EG and CG T-test: t(68) = -1.03; p > 0.05; Cohen d = 0.2. EG taught using GDIS outperformed those using TCM (ANCOVA: F = 361.49, p = 0.05). GDIS did not discriminate against gender in EG because no statistically significant differences in performance after the intervention (Mann Whitney U-test: U = 178.50, p = 0.58), suggesting that GDIS improved all learners' performance in chemistry, but not CTM. The findings provide teachers and stakeholders with empirical evidences on a strategy that improved learners' performance. Also, GDIS did not discriminate against gender like the TCM, suggesting that the strategy encourages girls to study science, which contributes to narrowing the existing gender gap of male and female in Science, Technology, Engineering and Mathematics (STEM) subjects.